1994
DOI: 10.1128/mcb.14.6.4160-4172.1994
|View full text |Cite
|
Sign up to set email alerts
|

m3G Cap Hypermethylation of U1 Small Nuclear Ribonucleoprotein (snRNP) In Vitro: Evidence that the U1 Small Nuclear RNA-(Guanosine-N2)-Methyltransferase Is a Non-snRNP Cytoplasmic Protein That Requires a Binding Site on the Sm Core Domain

Abstract: The RNA components of small nuclear ribonucleoproteins (U snRNPs) possess a characteristic 5'-terminal trimethylguanosine cap structure (m3G cap). This cap is an important component of the nuclear localization signal of U snRNPs. It arises by hypermethylation of a cotranscriptionally added m7G cap. Here we describe an in vitro assay for the hypermethylation, which employs U snRNP particles reconstituted in vitro from purified components and subsequent analysis by m3G cap-specific immunoprecipitation. Complemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…While pre‐immune serum did not reveal any signal, both immune sera revealed a similar pattern. As expected from its predicted role in snRNA cap modification (Mattaj, 1986; Plessel et al ., 1994), some signal was detected in the cytoplasm and this will be described in more detail elsewhere. In addition, the two antibodies labeled several bright spots in the nucleus, and double labeling with fibrillarin antibodies demonstrated that these were Cajal bodies (Figure 5B).…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…While pre‐immune serum did not reveal any signal, both immune sera revealed a similar pattern. As expected from its predicted role in snRNA cap modification (Mattaj, 1986; Plessel et al ., 1994), some signal was detected in the cytoplasm and this will be described in more detail elsewhere. In addition, the two antibodies labeled several bright spots in the nucleus, and double labeling with fibrillarin antibodies demonstrated that these were Cajal bodies (Figure 5B).…”
Section: Resultsmentioning
confidence: 76%
“…Other RNAs like tRNAs or SRP RNA are also thought to be matured in the nucleolus (Bertrand et al, 1998;Politz et al, 2000;Grosshans et al, 2001). Interestingly, in Archaea, some RNA precursors generate both snoRNA and either rRNA or tRNA (Ome et al, 2000;d'Orval et al, 2001;Tang et al, 2002).…”
Section: Assembly and Maturation Of U3 In Speci®c Nuclear Structuresmentioning
confidence: 99%
“…These proteins play a role in the biogenesis of the corresponding snRNPs. They associate with the U snRNAs in the cytoplasm, trigger snRNA cap hypermethylation and are part of the snRNP nuclear import signal (Mattaj et al ., 1993a; Plessel et al ., 1994). Yeast Sm proteins are also required for the stable accumulation of the associated U snRNAs in vivo (Rymond, 1993; Roy et al ., 1995; Bordonne and Tarassov, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The association of the common Sm core proteins with the Sm site of the snRNA occurs in the cytoplasm and is regulated by the survival motor neuron (SMN) complex and protein arginine methyltransferases (14)(15)(16)(17). The binding of the Sm core to the snRNA is required for the hypermethylation of the m 7 G cap structure to an m 3 G cap by the Tgs1 (trimethylguanosine synthase) hypermethylase (18)(19)(20) and for the 3 end trimming of the extra nucleotides by the TOE1 deadenylase (21,22).…”
Section: Introductionmentioning
confidence: 99%